PENGARUH LAPORAN KEUANGAN TERHADAP AKUNTABILITAS KINERJA PADA DINAS PENDIDIKAN KABUPATEN BANDUNG - Sakti, Fajar Tri; Masitoh, Siti (Faculty of SociaI and Political Sciences (FISIP), Universitas Islam Negeri (UIN) Bandung, 2018)
The level of effectiveness in the 2015-2016 LRA is still not able to fully use the funds available at the Bandung District Education Office. Based on the research that that the Financial Report consisting of Performance Accountability in Bandung District Education Office is significant with 6.088 because t count 6.088> t table 2.040 then the results are